Prediksi Potensi Kebangkrutan Dengan Menggunakan Metode Altman Z- Score - Lumban Tobing, Erwin Bernando (Universitas HKBP Nommensen, 2023)
This research aims to determine the potential for bankruptcy at PT Sri Rejeki Isman Tbk using the Altman Z-Score method for the 2018-2022 period. The population in this study is the Financial Report of PT Sri Rejeki Isman Tbk and the sample in this study is the Financial Report of PT Sri Rejeki Isman Tbk for the 2018-2022 period. This research uses quantitative descriptive analysis, namely analyzing and interpreting the results. The data collection technique used in this research is documentation by examining secondary data in the form of financial position reports, profit and loss reports and stock information obtained via the company website at https://www.sritex.co.id, the data processing technique used in the research This is a descriptive analysis and Modified Altman Z-Score analysis. The research results show that the company has a 2018 Z-Score of 3.59; in 2019 4.23; in 2020 3.76; in 2021 (14.37); in 2022 (3.16) with an average of (3.42) in the Danger Zone because the Z Score <1.1.